Pengaruh Model Pembelajaran dan Minat Belajar Terhadap Hasil Belajar Instalasi Motor Listrik - Suyitno M (JTP - Jurnal Teknologi Pendidikan, 2016)
The research aims to reveal the influence of learning model and learning interest on student’s installation of electric motors achievement. The research was conducted at SMK Dinamika Pembangunan Jakarta. The experiment was conducted using 2x2 factorial designs. The research concludes that: (1) installation of electric motors achievements of students who took part in Quantum Learning are higher than those who partipated in Expository model; (2) There is interaction between learning model and learning interest on student’s installation of electric motors achievement; (3) installation of electric motors achievement of the students having high learning interest and taking part in Expository Learning Model are higher than those participating in Quantum Learning Model; (4) installation of electric motors achievement of the students having low learning interest and taking part in Quantum Learning Model are higher than those participating in Expository Learning Model.